Global gender gap report 2021 (World Economic Forum, 2021)
Another generation of women will have to wait for gender parity, according to the World Economic Forum’s Global Gender Gap Report 2021. As the impact of the COVID-19 pandemic continues to be felt, closing the global gender gap has increased by a generation from 99.5 years to 135.6 years.
Keywords: OFDIG; approches et analyses; covid-19; discipline; inégalités; périodes historiques; ressource en ligne; sciences de la gestion; systèmes d'oppressions; économie; égalité des sexes